The waters of the river Pardo are very pure. Saturnino de Brito in the controversies about the springs of Ribeirão Preto - Deminici, Daniel (Risco - Journal of Architecture and Urbanism, 2016)
The appropriation of water resources was essential for the territorial formation of Ribeirão Preto since the rivers made it possible to set up the farms in the region. During the First Republic, when the urban core was consolidated at the junction of the tributaries of the river Pardo, the first controversies about the quality of the waters that would supply the city appear. On that occasion, the engineer Saturnino de Brito was invited to evaluate the water sources of the municipality. Thus, the article resumes some episodes of the appropriation of the water resources to make a reflection on the construction of the city.